Peer Role-Play for Training Communication Skills in Medical Students: A Systematic Review - Gelis, Anthony; Cervello, Sophie; Rey, Romain; Llorca, Guy; Lambert, Philippe; Franck, Nicolas; Dupeyron, Arnaud; Delpont, Marion; Rolland, Benjamin (Simulation in healthcare : journal of the Society for Medical Simulation, 2020)
Peer role-play (PRP) is a simulation-based training method (SBTM) in which medical students alternately play the patient's and clinician's role. This review aimed to assess the effectiveness of PRP for improving the communication skills of medical students. A systematic search was conducted in the MedLine, PsycInfo, and ERIC databases. Studies were qualitatively analyzed according to the Kirkpatrick evaluation level (Kirkpatrick level) and the Medical Education Research Study Quality Instrument.Twenty-two studies were included. Studies assessing the "reaction" of students (Kirkpatrick level 1, n = 15) found that PRP was appreciated, whereas those assessing the effect of PRP on "learning" (Kirkpatrick level 2, n = 12) found that PRP improves communication skills but no more than other SBTMs. No study assessed real-life "attitudes" or "clinical outcomes" (Kirkpatrick levels 3 and 4), whereas 2 studies found that using PRP had a better cost-efficacy ratio than the use of simulated patients. Compared with other SBTMs, PRP improved communication skills similarly in medical students and seemed less expensive.